(untitled) (Journal of Pedagogical Inventions and Practices, 2023)
One of the main tasks of special educational institutions is to provide students with the knowledge created throughout the history of mankind, to create appropriate conditions for regular knowledge of the basics of science, to select the necessary information and to meet their needs for learning by teaching them to study independently. is to satisfy and increase their interests. The unprecedented development of computer and software products opens wide opportunities for the use of information technologies in the natural sciences as well